Naomi Klein. The Shock Doctrine: The Rise of Disaster Capitalism. New York: Henry Holt and Metropolitan Books. 2007. 500 pages. Hardcover. US$18.11. (The Pakistan Development Review, 2010)
Naomi Klein is an award-winning journalist, and his book The Shock Doctrine: The Rise of Disaster Capitalism is a bestseller. Klein argues that free market philosophy professed by the Nobel laureate Milton Friedman and may others and adopted by the international financial institutions faced a hard time while being put to practice. Accordingly, crises were engineered in some countries to provide an environment in which unpopular reforms could be carried through. In some countries natural disasters were used as an occasion to push through the free market reform agenda. Klein’s basic thesis is that unpopular market reforms have typically been carried out at a time when the shock-stricken people were too disoriented to take even a clear stand on the reforms, much less to put up a stiff resistance to these. Policy changes that followed the Falklands war of 1982, the Tiananmen square event of 1989, the collapse of the Soviet Union in 1991, the Asian Financial Crisis of 1997, and of course the more recent Global Financial Crisis are all examples of pushing through the liberal reform agenda after the man-made crises had disoriented the public at large or had softened their stand on the free market.